KOMODIFIKASI KONTEN MEDIA PENYIARAN : ANALISIS EKONOMI POLITIK PADA MEDIA MASSA MNC GROUP - ZAHARA AUDINA; RIKA IFATI FARIHA (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2022)
Mass media is a topic that is always interesting to discuss, especially in its development in the industrial era 4.0 where technology is developing quite rapidly and can change various fields of life ranging from social, economic, political and others. As a result of this development, conventional media industries such as newspapers are starting to lag behind, this is due to changes in behavior in people who switch to the digital world. The exclusion of some print media in this industry proves that the changes that occur must be followed so that they do not become inanimate objects. The research method used in this journal is to collect data and literature related to the problems in this journal. The object of this research is MNC Group because Hary Tanoesoedibdjo is the owner of one of the largest television companies in Indonesia. The commodification of content was increasingly visible when Hari Tanoe joined as chairman of a political party, starting from the National Democrat Party to the current chairman of the new Party, Perindo. As the main owner of this television group, Hary can freely enter his opinion to be covered by their team. The result is that the commodification of broadcast media content at MNC Group is very clear, especially when Hary Tanoe enters the world of politics where his political perspectives and preferences influence how he behaves and makes policies through the power he has in his media to create content that benefits himself and the groups he supports.